Accounting Information System for Cash Receipts from Room Sales at The Pall Inn Hotel Cisarua - Putri, Risma Wandari; Triwidatin, Yuppy; Warizal (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Hotels play an important role in the tourism industry because improving hotel management is essential for developing the tourism sector. Good hotel management includes the use of effective, diverse, and accurate accounting information systems. These systems are needed to simplify and accelerate the accurate presentation of financial reports. From its main function, the primary product sold by hotel businesses is room rentals or lodging services. Therefore, it is crucial for companies to implement relevant accounting information systems that meet the hotel's needs, especially in managing financial matters. The purpose of this study is to examine the accounting information system for cash receipts from room sales at the Pall Inn Hotel Cisarua. This study uses a qualitative research design with descriptive analysis, focusing on the accounting information system for room sales and cash receipts applied at the Pall Inn Hotel Cisarua. The study's results indicate that the accounting information system for recording cash receipts is consistent with the theory of sales accounting information systems. The Pall Inn Hotel implements a computerized accounting system to ensure transparency and efficiency; however, improvements are needed in internal control, staff training, and system maintenance.